Clinical Use of Tumor Markers for the Detection and Prognosis of Bladder Carcinoma: A Comparison of CD44, Cytokeratin 20 and Survivin - Yikilmaz, Taha Numan; Dirim, Ayhan; Ayva, Ebru Sebnem; Ozdemir, Handan; Ozkardes, Hakan (Urology Journal, 2016)
Purpose: To investigate the role of CD44, cytokeratin 20 (CK20) and survivin for the detection and prognosis of patients with urothelial carcinoma of the bladder. Materials and Methods: The study included 82 patients who underwent transurethral resection of bladder tumors between 2009 and 2014. The patient and tumor characteristics with relevance to age, tumor size and focality, grade and stage, recurrence and progression were noted. Patients with carcinoma in situ, those who had at more than 3 sites of lesions and greater than 3 cm tumors were excluded. All cases were ex-smokers. All histological samples stained with hematoxylin and eosin were re-evaluated according to the 2004 World Health Organization/International Society of Urological Pathology (WHO/ISUP) classification system and immunohistochemically stained for CD44, CK20 and survivin. Results: The study group comprised 57 (69.5%) males and 25 (30.5%) females with a mean age of 60 years (range, 26-87 years). All were newly-diagnosed patients with bladder tumors. Immunohistochemical evaluation revealed that there was a statistically significant correlation between the grade and stage of the tumor with CK20 and survivin positivity (P < .05). As the grade and stage increased CD44 immunoreactivity significantly decreased (P = .002, P = .0001, respectively). However, relationship of protein expressions with recurrence and progression remained insignificant (P > .05). Conclusion: In cases of bladder urothelial carcinoma positivity for CD44, CK20, and survivin has significant relation with the tumor grade and stage while no significant relationship was determined in terms of recurrence and progression